2021
DOI: 10.1007/s00270-021-02875-5
|View full text |Cite
|
Sign up to set email alerts
|

A UK Expert Consensus Approach for Managing Symptomatic Arteriovenous Fistula (AVF) Stenosis in Haemodialysis Patients

Abstract: Purpose Stenoses in mature arteriovenous fistulas (AVFs) are common and can negatively impact on the quality of haemodialysis, the longevity of the AVF and lead to debilitating symptoms. Multiple treatment options exist; however, management can vary between different centres. We aimed to establish multidisciplinary consensus on the optimal stepwise application of interventions based on evidence and consensus. Methods A modified Delphi process was conducted with 13 participants from hospitals across the UK, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…K-DOQI (the National Kidney Foundation Kidney-Dialysis Outcomes Quality Initiative), CPM (Clinical Performance Measures), and other studies also emphasized that autologous AVF is the first choice for hemodialysis patients [ 13 ]. Although AVF is the most ideal vascular pathway for MHD patients, its service life is not permanent: a 2014 study showed that the 1- and 2-year patency rates of AVF were 60% and 51%, respectively [ 14 ]; data from the 2016 DOPSS (Dialysis Outcomes and Practice Pattern Study) showed that the patency rate of autologous AVF1 was only 68% in the UK and relatively high in Europe (83%) [ 15 ]. In addition, a systematic review in 2016 showed that only 62-68% of AVF remained unobstructed after 1 year of use and dropped to 38-56% after 2 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…K-DOQI (the National Kidney Foundation Kidney-Dialysis Outcomes Quality Initiative), CPM (Clinical Performance Measures), and other studies also emphasized that autologous AVF is the first choice for hemodialysis patients [ 13 ]. Although AVF is the most ideal vascular pathway for MHD patients, its service life is not permanent: a 2014 study showed that the 1- and 2-year patency rates of AVF were 60% and 51%, respectively [ 14 ]; data from the 2016 DOPSS (Dialysis Outcomes and Practice Pattern Study) showed that the patency rate of autologous AVF1 was only 68% in the UK and relatively high in Europe (83%) [ 15 ]. In addition, a systematic review in 2016 showed that only 62-68% of AVF remained unobstructed after 1 year of use and dropped to 38-56% after 2 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Reacting to flow changes could be burdensome and also not all stenotic lesions need to be addressed as some at the inflow could be protective from downstream adverse cardiovascular events. 21 Hence there is a need for a more comprehensive methodology to identify patients at risk for reinterventions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,8,10 The recently published British guidelines for managing AVF stenosis in haemodialysis patients recommended a lower threshold for the use of DCB across fistuloplasty amongst stenoses recurring between 3 and 12 months, with stenoses recurring after 12-months being treated as de novo lesions and recommending the use of POBA as first-line intervention. 11 The Ranger™ PCB (Boston Scientific, Marlborough, MA, USA) has a 'low' paclitaxel dose density of 2 μg/mm 2 and a lipohilipic acetyl tri-n-butyl citrate excipient. 12 Components of the PCB are built on the platform of the commercially available Sterling (0.018-inch wire-compatible) balloon dilation catheter (Boston Scientific, Marlborough, MA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8,10 The recently published British guidelines for managing AVF stenosis in haemodialysis patients recommended a lower threshold for the use of DCB across fistuloplasty amongst stenoses recurring between 3 and 12 months, with stenoses recurring after 12-months being treated as de novo lesions and recommending the use of POBA as first-line intervention. 11…”
Section: Introductionmentioning
confidence: 99%